Analisis Strategi Pemasaran Online Makanan Tradisional Khas Jambi (Studi Kasus Pada Pelaku UMKM Kota Jambi) - Mastuti HS; Syahmardi Yacob; Dahmiri Dahmiri (Universitas Batanghari Jambi, 2022)
This study aims to: 1) identify and analyze the perpetrators of traditional Jambi Malay traditional food MSME in competing to market their products online through SWOT analysis; 2) knowing and analyzing alternative online marketing strategies by traditional Jambi food MSME actors after knowing their competitive advantage position through SWOT matrix analysis; and 3) knowing and analyzing the role of traditional Jambi food MSME in improving the economy. To reveal these objectives, the researchers used qualitative research methods with a case study approach. The key informants in this study were the perpetrators of traditional Jambi food MSME in Jambi City who were taken by snowball sampling consisting of 11 key informants. Data sources or key informants are selected based on research needs. The results of the study show that: 1) The perpetrators of traditional Jambi food MSME in competing in marketing their products online through a SWOT analysis are divided into two analyzes, namely IFAS and EFAS; 2) alternative strategies, namely 1) Developing the potential for inferior product attractiveness in this case traditional Jambi food which has various types of food, 2) maintaining the authenticity and quality of Jambi traditional food products, 3) Increasing promotion of Jambi traditional food through strategies other online marketing apart from Instagram accounts, 4) setting quality standards for Jambi traditional food products, 5) monitoring the quality of Jambi traditional food products, 6) be honest and improve the quality of service, and 7) increasing offerings of Jambi traditional food products; 3) The role of Jambi Traditional Food MSME in Improving the Economy, namely 1) opening job opportunities for people who need work, 2) as a legacy business from generation to generation so that it becomes a relay for improving the family economy; 3) can increase revenue and; 4) provide education for family members and workers and their children from the results of this MSME business.